(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
This paper presents the development and evaluation of a VAT compliance model utilizing Hyperledger Fabric blockchain technology integrated with Monte Carlo simulations. The model aims to address the pervasive issue of VAT non-compliance by providing real-time monitoring and automated compliance checks. By simulating 10,000 VAT-related transactions under various compliance scenarios, the study assesses the model’s performance in detecting both compliant and non-compliant transactions based on product registration and VAT rate application. The Monte Carlo simulations generate diverse transaction scenarios, while the blockchain provides a secure, immutable ledger for tracking each transaction’s compliance status. The model is tested on a system simulating real-world conditions, focusing on key metrics such as transaction throughput, latency, accuracy, sensitivity, precision, and specificity. The results demonstrate that the model achieves 100% accuracy in identifying non-compliant transactions, with a transaction throughput of 1,200 transactions per second and an average latency of 0.83 milliseconds. This study highlights the potential of blockchain technology to revolutionize VAT administration by reducing non-compliance, enhancing transparency, and streamlining tax enforcement processes.